1996
DOI: 10.1161/01.str.27.3.467
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Measurement of Extracranial Internal Carotid Artery Stenosis as Displayed by Both Digital Subtraction and Magnetic Resonance Angiography

Abstract: Although observer variability in reporting can be considerable, no important differences were found among the different techniques widely used for measuring carotid stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 10 publications
1
24
1
1
Order By: Relevance
“…Recently, different measuring methods have been compared on angiograms. [3][4][5][6]27,28 Vanninen and colleagues compared ECST and NASCET methods and found the greatest interobserver variability with NASCET measurements. 27 Their findings are in agreement with those of Bladin and associates who also found NASCET to be the least reproducible method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, different measuring methods have been compared on angiograms. [3][4][5][6]27,28 Vanninen and colleagues compared ECST and NASCET methods and found the greatest interobserver variability with NASCET measurements. 27 Their findings are in agreement with those of Bladin and associates who also found NASCET to be the least reproducible method.…”
Section: Discussionmentioning
confidence: 99%
“…6,28 Rothwell and coworkers, Eliasziw and associates, and Young and colleagues compared reproducibility of ECST, NASCET, and CC methods. [3][4][5] Rothwell and coworkers recommended the CC method, because it showed the best reproducibility, particularly for lumen reduction in the clinically important range of 50 to 90%. Conversely, Eliasziw and associates and Young and colleagues reported no consistent differences between the measuring methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Although it has been reported that duplex US findings can be even more precised than angiographic findings 15 , the experiences from the NASCET (North American Symptomatic Carotid Endarterectomy Trial) and the Committee for the Asymptomatic Carotid Atherostenosis provide the rationale for performing carotid artery surgery, evolved from stenosis diameter measurements on angiograms. Which shows that the diameter of a stenosis measured at angiography remains the reference standard.…”
mentioning
confidence: 99%
“…16 -18 A population-based study using angiography would be unethical, and studies using Doppler or MR angiography would not allow such accurate measurements of all the bifurcation vessels. MR angiography is less accurate than arterial angiography, 19,20 and Doppler is often not able to image the internal carotid artery (ICA) distal to the bulb. 16,21 Thus, a large angiographybased study in a selected population would probably provide more reliable data on the extent of variation in carotid bifurcation anatomy than a smaller noninvasive, imagingbased study in the general population.…”
mentioning
confidence: 99%